TRPC absence induces pro-inflammatory macrophage polarization to promote obesity and exacerbate colorectal cancer - Lin, Yanting; Gao, Rui; Jing, Dongquan; Liu, Yiming; Da, Huijuan; Birnbaumer, Lutz; Yang, Yong; Gao, Xinghua; Gao, Zhenhua; Cao, Qiuhua (Frontiers in Pharmacology, 2024)
During the past half-century, although numerous interventions for obesity have arisen, the condition's prevalence has relentlessly escalated annually. Obesity represents a substantial public health challenge, especially due to its robust correlation with co-morbidities, such as colorectal cancer (CRC), which often thrives in an inflammatory tumor milieu. Of note, individuals with obesity commonly present with calcium and vitamin D insufficiencies.Transient receptor potential canonical (TRPC) channels, a subclass within the broader TRP family, function as critical calcium transporters in calcium-mediated signaling pathways. contributing to CRC development. This study provides valuable insights into the role and underlying mechanisms of TRPC deficiency in obesity and its related complication, CRC.Our findings offer a theoretical foundation for the prevention of adverse effects associated with TRPC inhibitors, potentially leading to new therapeutic strategies for obesity and CRC prevention.